1996
DOI: 10.1172/jci118576
|View full text |Cite
|
Sign up to set email alerts
|

Presence of hypochlorite-modified proteins in human atherosclerotic lesions.

Abstract: Oxidation of LDL may contribute to atherogenesis, though the nature of the in vivo oxidant(s) remains obscure. Myeloperoxidase, the enzyme responsible for hypochlorous acid/hypochlorite (HOCl) production in vivo, is present in active form in human atherosclerotic lesions, and HOCl aggregates and transforms LDL into a high-uptake form for macrophages in vitro. Here we demonstrate HOCl-modified proteins in human lesions using an mAb raised against HOCl-modified LDL that recognizes HOCl-oxidized proteins but does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
363
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(385 citation statements)
references
References 32 publications
14
363
0
1
Order By: Relevance
“…[261]). Studies on hypochlorite-oxidized protein, in which antisera specificities have been carefully validated, suggest not only that hypochlorite-oxidized proteins are present in plaques, but also that apoB peptides are among them [262]. HOCl appears to attack the protein selectively [97,263].…”
Section: Atherosclerosismentioning
confidence: 99%
“…[261]). Studies on hypochlorite-oxidized protein, in which antisera specificities have been carefully validated, suggest not only that hypochlorite-oxidized proteins are present in plaques, but also that apoB peptides are among them [262]. HOCl appears to attack the protein selectively [97,263].…”
Section: Atherosclerosismentioning
confidence: 99%
“…It catalyzes the two-electron peroxidation of chloride to generate hypochlorous acid (HOCl) [2], a potent chlorinating oxidant, capable of chlorinating tyrosine into chlorotyrosine. Levels of chlorotyrosine are increased in atherosclerotic tissues [3] and the blood of in patients with inflammatory conditions including atherosclerosis [4,25,26]. The chlorination of apolipoprotein A-I was found to impair its cardioprotective ability to remove excess cellular cholesterol from lipid-laden macrophages in the artery wall [5].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been obtained for the modification of ECM components by MPO-derived oxidants in human atherosclerotic lesions by use of a monoclonal antibody (HOP-1) raised against HOCldamaged LDLs. This antibody does not recognize proteins oxidized by a wide variety of other oxidants in itro [39]. Application of this antibody resulted in significant staining of both intra-and extra-cellular locations, particularly in the intimal area and at cholesterol clefts, with little staining detected in normal human artery samples [39].…”
Section: Introductionmentioning
confidence: 99%
“…This antibody does not recognize proteins oxidized by a wide variety of other oxidants in itro [39]. Application of this antibody resulted in significant staining of both intra-and extra-cellular locations, particularly in the intimal area and at cholesterol clefts, with little staining detected in normal human artery samples [39]. Recent studies have demonstrated that the intensity of staining induced by this antibody correlates with intimal thickening in lesions of differing severity, suggesting that the MPO-induced damage plays a role in lesion development [40].…”
Section: Introductionmentioning
confidence: 99%